ECOLOGY OF THE DUGONG AND ITS MANAGEMENT - Nishiwaki, Masaharu (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Today, many people know that the mythical mermaids of legendal stories originated from the animals belonged to the order Sirenia. Sirenians can be devided into two groups, manatees of the Atlantic coasts and the dugong of the IndoPacific area. Table I shows the present living species belong to the order Sirenia.